Features of Investments in Different Periods of a Person's Life Cycle - Ikromovna, Khasanova Aziza (Researchparks Publishing, 2023)
This article provides theoretical and practical information about the theoretical interpretation of the concept of human capital, the characteristics of investments in different periods of the human life cycle in its development, and developed appropriate proposals.